2015
DOI: 10.1007/s10517-015-3053-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NMDA, a Specific Agonist to NMDA Receptor Complex, on Rat Hippocampus

Abstract: Removal of Mg2+ ions from perfusion medium provoked epileptiform activity in CA1 field of surviving rat hippocampal slices manifested in generation of extra population spikes. MK-801 (100 μM), a specific non-competitive antagonist to NMDA-receptor complex, prevented this effect. NMDA (20 μM), the specific agonist to this complex, produced no significant effect on the orthodromic population spikes, but when applied at concentrations of 30 or 40 μM, it inhibited them partially (by 21-28%) or almost completely (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The underlying mechanisms may be associated with the activation of NMDAR. NMDA activate NMDAR on hippocampal neurons, change synaptic plasticity and release excitatory neurotransmitters that condition and inhibit MK-801 in a non-competitive role to improve cell vitality ( 28 , 29 ). A further study has revealed that MK-801 treatment [0.2 mg/kg, intraperitoneal (IP)] increases NSC proliferation in the hippocampus of a rat model with Parkinson's disease ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms may be associated with the activation of NMDAR. NMDA activate NMDAR on hippocampal neurons, change synaptic plasticity and release excitatory neurotransmitters that condition and inhibit MK-801 in a non-competitive role to improve cell vitality ( 28 , 29 ). A further study has revealed that MK-801 treatment [0.2 mg/kg, intraperitoneal (IP)] increases NSC proliferation in the hippocampus of a rat model with Parkinson's disease ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…NMDARs are glutamate ionotropic receptors that play an important role in synaptic transmission and plasticity. Some NMDAR antagonists were identified to rapidly induce antidepressant effect by instant upregulation of expression of BDNF and spine formation [ 14 , 15 ]. Therefore, enhancement of neural plasticity can result from activation of PKA-CREB or inhibition of NMDA signaling.…”
Section: Introductionmentioning
confidence: 99%
“…The NMDARs stimulation induces the influx of Ca 2+ through NMDARs and activates CaMKII, which then activates the RhoA-Rho-kinase pathway [7,11]. The NMDA (an NMDAR agonist) and high K + induced the CamKII autophosphorylation at Thr286 downstream of NMDARs [19,20]. To evaluate whether Rho-kinase phosphorylates PSD-93 downstream of NMDARs, striatal slices were treated with high K + or NMDA to induce Ca 2+ influx through NMDARs.…”
Section: Rho-kinase Phosphorylates Psd-93 At Thr612 In Striatal Slicesmentioning
confidence: 99%